2008
DOI: 10.1016/j.aca.2008.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of cell aging and ATP release from erythrocytes and its implications in type 2 diabetes

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) is a determinant in the antioxidant status of the red blood cell (RBC) and is also used as an indicator of cell age. However, it is unknown if the relationship between antioxidant status, cell age, and RBC-derived adenosine triphosphate (ATP) occurs immediately or over a period of time. Therefore, the development of a simultaneous determination of G6PD activity (via the determination of nicotinamide adenine dinucleotide phosphate (NADPH)) in RBCs and the determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 32 publications
7
45
1
Order By: Relevance
“…Notably, ATP concentration in trophocytes and fat cells have also been shown to decrease with advancing age in worker bees reared in a thermostatic chamber at 34°C (Hsu and Chan 2011a), providing further support for the idea that young and old workers reared in a field hive can be used for studying aging. This decrease in ATP concentration in trophocytes and fat cells of older workers is also consistent with previous studies showing that ATP levels decrease with advancing age in the gastric mucosa and muscle of humans (Kawano et al 1991;Conley et al 2000;Petersen et al 2003;Gurd et al 2008), the blood and brains of mice (Jayachandran et al 2005;Joo et al 1999), the erythrocytes of rabbits (Subasinghe and Spence 2008) and cows (Bartosz et al 1982), and the hearts of rats (Guerrieri et al 1996). This finding is also consistent with the results of ΔΨm measurements reported in this study; as was the case for NAD + , a decrease in ΔΨm can result in a decrease in ATP concentration.…”
Section: δψMsupporting
confidence: 92%
“…Notably, ATP concentration in trophocytes and fat cells have also been shown to decrease with advancing age in worker bees reared in a thermostatic chamber at 34°C (Hsu and Chan 2011a), providing further support for the idea that young and old workers reared in a field hive can be used for studying aging. This decrease in ATP concentration in trophocytes and fat cells of older workers is also consistent with previous studies showing that ATP levels decrease with advancing age in the gastric mucosa and muscle of humans (Kawano et al 1991;Conley et al 2000;Petersen et al 2003;Gurd et al 2008), the blood and brains of mice (Jayachandran et al 2005;Joo et al 1999), the erythrocytes of rabbits (Subasinghe and Spence 2008) and cows (Bartosz et al 1982), and the hearts of rats (Guerrieri et al 1996). This finding is also consistent with the results of ΔΨm measurements reported in this study; as was the case for NAD + , a decrease in ΔΨm can result in a decrease in ATP concentration.…”
Section: δψMsupporting
confidence: 92%
“…ATP concentration decreases with age in the gastric mucosa and muscle of humans (Kawano et al 1991;Gurd et al 2008), the blood and brain of mice (Jayachandran et al 2005;Joo et al 1999), the erythrocytes of rabbits (Subasinghe and Spence 2008) and cows (Bartosz et al 1982), and the heart of rats (Guerrieri et al 1996). Similarly, we have found that ATP concentration decreases with age in the trophocytes and oenocytes of worker bees (Hsu and Chan 2013;Chuang and Hsu 2013).…”
Section: Nad + Nadh and Atp Concentrationsmentioning
confidence: 52%
“…The released ATP from RBCs, for example, binds and activates the purinergic G protein-coupled receptors (P2Y receptors) on vascular endothelial cells and induces the synthesis and release of nitric oxide (12,13), a well-known vasodilator. Moreover, impaired release of ATP from RBCs has been linked to diseases, such as type II diabetes and cystic fibrosis (14,15). Given that RBCs experience shear stresses continuously during the circulation cycle and that the released ATP plays a central role in vascular pathophysiology, understanding of the mechanotransductive release of ATP from RBCs will provide not only fundamental insights to the roles of RBCs in vascular homeostasis but also, potential therapeutic strategies for red cell dysfunction and vascular disease.…”
mentioning
confidence: 99%